Vacuum system integrated additive manufacturing: a new approach to improve 3D printed parts tensile strength - Wong, John Huang Ung; Maidin, Shajahan (Penerbit UTeM Press, 2023)
An investigation of the weakest zone in vacuum-assisted FDM for additive manufacturing. Vacuum-assisted FDM can improve the tensile strength of printed parts by reducing convective heat transfer in a vacuum environment. The z-axis was found to be weakest at the layer-by-layer bonding. The study was carried out to improve the strength of additive manufacturing.